Spillovers Across NAFTA - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2008)
This paper examines linkages across North America by estimating the size of spillovers from the major regions of the world-the United States, euro area, Japan, and the rest of the world-to Canada and Mexico, and decomposing the impact of these spillovers into trade, commodity price, and financial market channels. For Canada, a one percent shock to U.S. real GDP shifts Canadian real GDP by some 3/4 of a percentage point in the same direction- with financial spillovers more important than trade in recent decades. Thus, a large proportion of the reduction in Canadian output volatility since the 1980s can be accounted for by the "Great Moderation" in U.S. growth. Before 1996, domestic volatility in Mexico swamped the contribution of external factors to the business cycle. After 1996, the response of Mexican GDP is 1 1\2 times the size of the U.S. shock-"when the U.S. sneezes, Mexico catches a cold". These spillovers are transmitted through both trade and financial channels.